PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY AR PADA MATA PELAJARANDASAR – DASAR PROGRAM KEAHLIAN DDPK KELAS X DI SMK N 1 RAO SELATAN - Saputra, Randa Dwi; Alfiriani, Adlia; Pratama, Ade (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research aims to develop interactive media in learning drawing sketches in class The background of this research is based on students' low interest and learning motivation in understanding drawing sketch theory material due to the lack of use of interactive media in the learning process. The research method used is Research and Development (RD) with the ADDIE development model which consists of five stages: analysis, design, development, implementation and evaluation. Interactive media was developed using the Articulate Storyline 3 application and converted into an Android application (.apk), so that students can access it anytime and anywhere. Validation results by media experts show that interactive media has a validity level of 88.02% in the very valid category, while validation by material experts got a score of 84.62% which is also in the suitable for use category. Furthermore, the practicality test by the teacher obtained a result of 89%, and the practicality test by students reached 85%, both of which fall into the very practical category. Thus, the interactive media developed can be a solution in increasing students' interest, motivation and understanding of sketch drawing material.